Caracterización fisicoquímica del fruto del níspero Bellucia spruceana. para la obtención de pectina - Pezo Pinedo, Percy (2023)
The research has a quantitative orientation, descriptive at an experimental level, its objective was the physicochemical characterization of the fruit of the loquat Bellucia spruceana, to obtain pectin. The study population consisted of the fruits of the medlar Bellucia spruceana, from the trees located along the Iquitos-Nauta highway axis; Non-random sampling was considered in the opinion of the executors; 3 kg of semi-ripe fruits were used as the sample size. Pectin extraction was carried out using citric acid as an extracting agent at pH 2.5, 3 and 3.5 witha duration of 80 minutes of acid hydrolysis, at temperatures of 70, 80 and 85°C, with a 32 -factorial design. A higher yield of 18.43% pectin (pH 2.5 and 85°C), in a time of 80 minutes. To evaluate its quality, physicochemical characterization was carried out, classifying it as high methoxyl. In conclusion, it can be deduced that it is possible to obtain pectin from the fruits of the loquat Bellucia spruceana.